The Influence of Aging of P Fertilizer and Rainfall on the Yield and P Uptake by Setaria - Aminuddin, H.; Vanderdeelen, J. (1987)
An experiment to look into the influence of aging of phosphorus (P) fertilizer, P forms, P levels and rainfall on the yield and P uptake by pasture grass Setaria splendida on a Bungor Series soil (Typic Paleudult) was carried out. It was concluded that P treatment levels have more influence than the aging and forms of P fertilizer used on the dry matter yield and P uptake by Setaria. Variations in rainfall during the growing period of Setaria could account for up to a difference of39% in dry matter yield and 20% of the P taken up.